Performance evaluation of relationa embedded databases: an empirical study - Hassan, Hassan B.; Sarhan, Qusay I. (Innovaciencia, 2018)
Introduction: With the rapid deployment of embedded databases across a wide range of embedded devices such as mobile devices, Internet of Things (IoT) devices, etc., the amount of data generated by such devices is also growing increasingly. For this reason, the performance is considered as a crucial criterion in the process of selecting the most suitable embedded database management system to be used to store/retrieve data of these devices. Currently, many embedded databases are available to be utilized in this context. Materials and Methods: In this paper, four popular open-source relational embedded databases; namely, H2, HSQLDB, Apache Derby, and SQLite have been compared experimentally with each other to evaluate their operational performance in terms of creating database tables, retrieving data, inserting data, updating data, deleting data. Results and Discussion: The experimental results of this paper have been illustrated in Table 4. Conclusions: The experimental results and analysis showed that HSQLDB outperformed other databases in most evaluation scenarios.